ANALISIS EXPERIENTIAL MARKETING, BRAND TRUST DAN SERVICE QUALITY TERHADAP LOYALITAS KONSUMEN DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING - Zai'mah, Amirotuz; Harli Ristifani, Zanuar (Journal of Islamic enterpreneurship and Management, 2023)
This research aims to determine the influence of Experiential Marketing, Islamic Business Ethics and Service Quality on Consumer Loyalty with Consumer Satisfaction as an Intervening Variable (Case Study of Consumers of the Abadi Motor Dealer in Ambarawa, Semarang Regency). This type of research is quantitative research. Meanwhile, the sample selection for this research was determined using the purposive random sampling method, which obtained a sample of 98 respondents for the 2016-2021 observation period. The analytical methods used include descriptive statistical tests, stationarity tests, T tests, F tests, coefficient of determination (R2), classical assumption tests and path analysis. This research uses the SPSS 23 data analysis method. The results of the research show that experiential marketing has no significant effect on consumer satisfaction, Islamic business ethics has a positive and significant effect on consumer satisfaction, service quality has a positive and significant effect on consumer satisfaction. Experiential marketing has a positive and significant effect on consumer loyalty, Islamic business ethics has a positive and significant effect on consumer loyalty, service quality has no significant effect on consumer loyalty. Consumer satisfaction has a positive and significant effect on consumer loyalty. Experiential marketing has no significant effect on consumer loyalty with consumer satisfaction as an intervening variable, Islamic business ethics has a positive and significant effect on consumer loyalty with consumer satisfaction as an intervening variable, service quality has a positive and significant effect on consumer loyalty with consumer satisfaction as an intervening variable.